2020
DOI: 10.1038/s41467-020-18831-9
|View full text |Cite
|
Sign up to set email alerts
|

Well-being as a function of person-country fit in human values

Abstract: It is often assumed that incongruence between individuals’ values and those of their country is distressing, but the evidence has been mixed. Across 29 countries, the present research investigated whether well-being is higher if people’s values match with those of people living in the same country or region. Using representative samples, we find that person-country and person-region value congruence predict six well-being measures (e.g., emotional well-being, relationship support; N = 54,673). Crucially, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
1
20
0
2
Order By: Relevance
“…Our results are consistent with the existing research that found a positive effect of certain human values on the attitudes and behaviors of employees. For example, human values determine employee attitudes and behaviors [55,67,68]. Regarding the main object of this research, we found that workers with collectivist values (benevolence and universalism) and who are focused on openness to change (stimulation and selfdirection) are more likely to develop green attitudes, which in turn can lead to greater well-being.…”
Section: General Findingsmentioning
confidence: 75%
“…Our results are consistent with the existing research that found a positive effect of certain human values on the attitudes and behaviors of employees. For example, human values determine employee attitudes and behaviors [55,67,68]. Regarding the main object of this research, we found that workers with collectivist values (benevolence and universalism) and who are focused on openness to change (stimulation and selfdirection) are more likely to develop green attitudes, which in turn can lead to greater well-being.…”
Section: General Findingsmentioning
confidence: 75%
“…This means that we considered only p-values of < .003 as statistically significant. This is a standard procedure for studies that involve many variables to ensure reliable results, e.g., [42]. Note that changing the «-threshold impacts the test statistic (e.g., t -value), as the test statistic and p-value are perfectly associated with any given sample size [43].…”
Section: B Correlates Of Activitiesmentioning
confidence: 99%
“…On the one hand, cultural contexts seem to moderate individual-level associations between personal values and psychological outcome variables (Heim et al, 2019 ; Sortheix & Lönnqvist, 2013 ; Sortheix & Schwartz, 2017 ). Previous studies have found that value-environment fit has positive implications for individual mental health and well-being (Hanel et al, 2020 ). Researchers have identified four potential pathways through which contexts influence the link between personal values and well-being: social sanctions, environmental affordances, internal conflict, and shared realities (Edwards & Cable, 2009 ; Fulmer et al, 2010 ; Sagiv & Schwartz, 2000 ).…”
Section: Introductionmentioning
confidence: 97%